Editorial Welcome: Launching the American Journal of STEM Education: Issues and Perspectives - Gaulee, Uttam; Bista, Krishna (American Journal of STEM Education, 2024)
This editorial introduces the inaugural volume of the American Journal of STEM Education: Issues and Perspectives, a peer-reviewed platform designed to advance knowledge, research, and practices within the field of STEM education. The journal addresses key gaps in disseminating interdisciplinary STEM education research and promotes best practices, equity, and innovation in teaching and learning. The mission and scope of the journal are to emphasize its commitment to supporting graduate students and early-career scholars through dedicated mentorship and publishing opportunities. The journal’s first issue features empirical research and reviews on diverse topics, including graduation trends, technology-enhanced pedagogy, equitable administration practices, the integration of generative AI in international education, and the impact of disruptive technologies in community colleges. Through its interdisciplinary approach, the journal aims to foster dialogue and contribute globally to the continuous improvement of STEM education.